Advanced nitrogen removal from low C/N municipal wastewater by combining partial nitrification-anammox and endogenous partial denitrification-anammox (PN/A-EPD/A) process in a single-stage reactor. (November 2021) - Cui, Huihui; Zhang, Liang; Zhang, Qiong; Li, Xiyao; Huang, Yu; Peng, Yongzhen
Graphical abstract: Highlights: PN/A-EPD/A process was developed in an IFAS-SBR treating real municipal wastewater. High NRE of 90.1% was achieved under aerobic HRT of 8 h and DO of 0.4 ± 0.1 mg/L. 89.9% of TN was removed by anammox pathway in typical cycle. Relative abundance of Candidatus Brocadia rose from 0% to 0.79% in suspended sludge. Abstract: In this study, an innovative partial nitrification-anammox (PN/A) and endogenous partial denitrification-anammox (EPD/A) process was developed in a single-stage integrated fixed film activated sludge sequencing batch reactor (IFAS-SBR) treating real municipal wastewater with C/N ratio below 3.2. Enhanced efficiency of total nitrogen (TN) removal reached 90.1% with low HRT of 12 h and DO of 0.4 ± 0.1 mg/L. Detailed nitrogen removal mechanism analysis of typical cycle revealed that 89.9% of TN was eliminated through anammox pathway. Anammox bacteria ( Candidatus Brocadia ) and endogenous denitrifying bacteria ( Candidatus Competibacter ) were abundant both in biofilms and suspended sludge, meanwhile ammonium-oxidizing bacteria has outcompeted nitrite-oxidizing bacteria, which all favored the synergistic effect of anammox with PN and EPD and contributed to the improvement of nitrogen removal. Overall, the above results confirmed that combined PN/A and EPD/A process is a reliable and efficient alternative for mainstream anammox process.